A new 3‐D thin‐skinned rock glacier model based on helicopter GPR results from the Swiss Alps. Issue 11 (8th June 2015) - Merz, Kaspar; Green, Alan G.; Buchli, Thomas; Springman, Sarah M.; Maurer, Hansruedi
Abstract: Mountainous locations and steep rugged surfaces covered by boulders and other loose debris are the main reasons why rock glaciers are among the most challenging geological features to investigate using ground‐based geophysical methods. Consequently, geophysical surveys of rock glaciers have only ever involved recording data along sparse lines. To address this issue, we acquired quasi‐3‐D ground‐penetrating radar (GPR) data across a rock glacier in the Swiss Alps using a helicopter‐mounted system. Our interpretation of the derived GPR images constrained by borehole information results in a novel "thin‐skinned" rock glacier model that explains a concentration of deformation across a principal shear zone (décollement) and faults across which rock glacier lobes are juxtaposed. The new model may be applicable to many rock glaciers worldwide. We suggest that the helicopter GPR method may be useful for 3‐D surveying numerous other difficult‐to‐access mountainous terrains. Key Points: First ever quasi‐3‐D helicopter GPR survey of an Alpine rock glacier Active rock glacier units are identified on geophysical images New thin‐skinned rock glacier model is proposed